Beyond the Worship Wars: Building Vital and Faithful Worship - Long, Thomas G. (Rowman & Littlefield Publishers, 2001)
Almost every congregation is experiencing tension over worship. Many congregations have been participating in a renaissance of worship known as the "liturgical movement" and have reclaimed worship forms that have served the church for centuries. Yet because the church today is operating in a radically changed cultural environment, many people in our society do not understand liturgical worship and thus we must find language, music, themes, and images that speak to the unchurched, spiritually seeking person. In Beyond the Worship Wars, Thomas G. Long discusses the nine characteristics of vital and faithful worship practiced by a wide range of "third-way" congregations—all characteristics that make for vital and faithful worshi